Planificación tributaria y cumplimiento del pago de tributos en la empresa Transportes y Servicios Fluviales Golfinho SAC Iquitos 2020 - Ruesta Barrera, Aldo Anderson (2022)
The general objective of this study was to determine the relationship between tax planning and tax payment compliance in the company Transportes y Servicios Fluviales Golfinho SAC, Iquitos 2020, opting for an applied type study, correlational level and non-experimental design, to 11 workers of said company were included as a sample, who were surveyed through a questionnaire that analyzes their perception regarding the variables evaluated, for which I conclude that tax planning is regular because sometimes it permanently supervises each one of the processes, in addition, that never have all the responsibilities for each position well defined. Likewise, compliance with the payment of taxes, because accounting strategies to avoid tax penalties are almost never known, on the other hand, sometimes it complies with the issuance of vouchers legally established in the country. Finally, it has been determined that there is a relationship between tax planning and compliance with the payment of taxes in the company transportation and river services Golfinho SAC Iquitos 2020, approved with a significance (bilateral) of 0.000 and a Pearson correlation of 0.927 being positive very strong .